2013
DOI: 10.5012/bkcs.2013.34.11.3335
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent Photoluminescence of Boron-doped ZnO Nanorods

Abstract: Boron-doped ZnO (BZO) nanorods were grown on quartz substrates using hydrothermal synthesis, and the temperature-dependence of their photoluminescence (PL) was measured in order to investigate the origins of their PL properties. In the UV range, near-band-edge emission (NBE) was observed from 3.1 to 3.4 eV; this was attributed to various transitions including recombination of free excitons and their longitudinal optical (LO) phonon replicas, and donor-acceptor pair (DAP) recombination, depending on the local l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Additionally, nitrogen-or boron-associated ZnO luminescence was not observed from the high-resolution photoluminescence spectroscopic analyses (Supplementary Figure S5). 39,40 This suggested that the atoms in hBN were not incorporated into the ZnO nanostructures during the vdW-MOVPE process.…”
Section: Nanoarchitectural Vdw Heteroepitaxy Of Zno On Hbnmentioning
confidence: 99%
“…Additionally, nitrogen-or boron-associated ZnO luminescence was not observed from the high-resolution photoluminescence spectroscopic analyses (Supplementary Figure S5). 39,40 This suggested that the atoms in hBN were not incorporated into the ZnO nanostructures during the vdW-MOVPE process.…”
Section: Nanoarchitectural Vdw Heteroepitaxy Of Zno On Hbnmentioning
confidence: 99%
“…The strongest maximum is related not only to NBE processes but also transitions related to free exiton relaxation, longitudinal optical (LO)-phonon replicas, free-to-neutral acceptor transitions, etc. [38]. so the value differs slightly from 3.22-3.24 eV typical for ZnO.…”
Section: Resultsmentioning
confidence: 87%
“…The deep-level characteristic green emission band is found at 498 ± 10 nm (2.43-2.54 eV). The green band is originated from intrinsic V Zn , V O and Z i defects [38,39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong and narrow UV emission peak, centered at 3.24 eV for all cases, results from merging of the various exciton-related emission near the band-edge, including recombination of free excitons and its longitudinal optical (LO)-phonon replicas, [33] free-to-neutral acceptor transitions, [34] and donor-acceptor pair recombination, [35] depending on the local lattice configuration and the presence of defects. [36][37][38] The strong and narrow UV emission peak, centered at 3.24 eV for all cases, can be assigned to the donor-acceptor transition. From the Figure 2a, we can also observe a broad visible level emission that expands from green to orange color wavelength.…”
Section: Resultsmentioning
confidence: 99%